2016
DOI: 10.1097/md.0000000000002650
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acute Kidney Injury After Robot-Assisted Laparoscopic Radical Prostatectomy Versus Retropubic Radical Prostatectomy

Abstract: Acute kidney injury (AKI) is associated with extended hospital stay, a high risk of progressive chronic kidney diseases, and increased mortality. Patients undergoing radical prostatectomy are at increased risk of AKI because of intraoperative bleeding, obstructive uropathy, older age, and preexisting chronic kidney disease. In particular, robot-assisted laparoscopic radical prostatectomy (RALP), which is in increasing demand as an alternative surgical option for retropubic radical prostatectomy (RRP), is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 41 publications
3
53
2
Order By: Relevance
“…[ 26 – 28 ] The overall incidence of AKI after RALP is reported to be approximately 5.5%. [ 5 ] In our present study, the incidence of postoperative AKI in RALP was 5.1%. Postoperative AKI is defined as an abrupt decrease of renal function, [ 29 ] and is associated with increased health costs, morbidity, and mortality.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…[ 26 – 28 ] The overall incidence of AKI after RALP is reported to be approximately 5.5%. [ 5 ] In our present study, the incidence of postoperative AKI in RALP was 5.1%. Postoperative AKI is defined as an abrupt decrease of renal function, [ 29 ] and is associated with increased health costs, morbidity, and mortality.…”
Section: Discussionsupporting
confidence: 47%
“…[ 4 ] In addition, postoperative acute kidney injury (AKI) occurs at a lower incidence after RALP than after open retropubic radical prostatectomy. [ 5 ] However, postoperative AKI is linked to increased morbidity, mortality, and health costs in hospitalized patients. [ 6 , 7 ] Therefore, the prevention of postoperative AKI is important for improving the postoperative outcomes of robotic prostatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies specifically examined the incidence of AKI across the differing techniques and included analysis of diagnostic studies. [68][69][70] AKI occurred in these three studies conforming to the acute kidney injury network stage-1 criteria regarding increase in serum creatinine (either absolute increase of ! 0.3 mg dL À1 or !1.5-fold increase from baseline), or decrease in urine output (<0.5 mL kg À1 h À1 for >6 h) with a reported incidence of 5.5-6.5% across robotic cases.…”
Section: Acute Kidney Injurymentioning
confidence: 96%
“…0.3 mg dL À1 or !1.5-fold increase from baseline), or decrease in urine output (<0.5 mL kg À1 h À1 for >6 h) with a reported incidence of 5.5-6.5% across robotic cases. [68][69][70] Among the studies examined there was no clear relationship regarding the incidence of AKI with surgical technique, with some studies finding a lowered incidence in robotic cases, that was thought to relate to decreased blood loss and blood transfusions administered. 68 70 One paper mentioned a total of 17 in 293 cases (5.8%) without reference to specific criteria.…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…The incidence of acute kidney injury (AKI) in patients who undergo NSS remains controversial. Studies have shown that overall incidence of AKI, measured either as an increase in serum creatinine or fall in urine output, is 5.5–6.5% across RAPN cases [40] , [41] . The suggested preventative non-surgical strategies include aggressive fluid hydration to produce a diuresis of >200 mL/h [42] and to keep the pneumoperitoneum pressures at ≤15 mmHg [43] .…”
Section: Surgical Factorsmentioning
confidence: 99%